Matter’s Performance in Christoph Schlingensief’s “Animatographische Editionen” - Pollock, Katherine (Studia Germanica Posnaniensia, 2022)
German director Christoph Schlingensief’s Animatographische Editionen (2004-06) included a series of three geographically-distinct labyrinthine walkthrough installations with a constellation of rooms and rotating platforms, leading to an Animatograph – a spinning carousel of material upon which videos were projected. Diverging from the current tendency in Schlingensief scholarship towards Niklas Luhmann’s systems theory, this paper focuses on the role of material in the Animatograph to show how it sympoietically enfolds autopoietic systems of communication. In particular, I investigate how humans explored the installations’ tight spaces, foul smells, swirling sights and cacophony of sounds, transforming materials and animals into performers. To do so, I derive concepts from Rebecca Schneider, Karen Barad and Donna Haraway to argue that in the encounter with the human, matter looks, touches back, and performs. In addition to providing a compelling site to investigate the intra-active entanglements of humans, animals, and materials in an aesthetic context, Schlingensief’s Animatograph allows us to see the ongoing (re)configuration of these entanglements, putting posthumanist performativity on display and highlighting the aesthetic contributions of the non-human.